Boreal forest soil carbon fluxes one year after a wildfire: Effects of burn severity and management. (10th June 2021) - Kelly, Julia; Ibáñez, Theresa S.; Santín, Cristina; Doerr, Stefan H.; Nilsson, Marie‐Charlotte; Holst, Thomas; Lindroth, Anders; Kljun, Natascha
Abstract: The extreme 2018 hot drought that affected central and northern Europe led to the worst wildfire season in Sweden in over a century. The Ljusdal fire complex, the largest area burnt that year (8995 ha), offered a rare opportunity to quantify the combined impacts of wildfire and post‐fire management on Scandinavian boreal forests. We present chamber measurements of soil CO2 and CH4  fluxes, soil microclimate and nutrient content from five Pinus sylvestris sites for the first growing season after the fire. We analysed the effects of three factors on forest soils: burn severity, salvage‐logging and stand age. None of these caused significant differences in soil CH4 uptake. Soil respiration, however, declined significantly after a high‐severity fire (complete tree mortality) but not after a low‐severity fire (no tree mortality), despite substantial losses of the organic layer. Tree root respiration is thus key in determining post‐fire soil CO2 emissions and may benefit, along with heterotrophic respiration, from the nutrient pulse after a low‐severity fire. Salvage‐logging after a high‐severity fire had no significant effects on soil carbon fluxes, microclimate or nutrient content compared with leaving the dead trees standing, although differences are expected to emerge in the long term. In contrast, the impact of stand age was substantial: a young burnt stand experienced more extreme microclimate, lower soil nutrient supply and significantly lower soil respiration than a mature burnt stand, due to a thinner organic layer and the decade‐long effects of a previous clear‐cut and soil scarification. Disturbance history and burn severity are, therefore, important factors for predicting changes in the boreal forest carbon sink after wildfires. The presented short‐term effects and ongoing monitoring will provide essential information for sustainable management strategies in response to the increasing risk of wildfire. Abstract : In 2018, an extreme drought led to the worst wildfire season in Sweden in over a century, and the Ljusdal fire was the largest area burnt that year. We investigated the impacts of burn severity, salvage‐logging and stand maturity on soil carbon fluxes in the first year after the fire. Burn severity and stand maturity were key drivers of soil CO2  fluxes; salvage‐logging (after high‐severity fire) had no impact; and none of the factors affected the soil CH4 uptake.